DIRECTLY ELECTED PRESIDENT OF THE REPUBLIC AND HIS CRIMINAL LIABILITY - Pejić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Conceptualizing and defining the executive power, particularly the presidency as its primary exponent, is a pressing issue in constitutional systems that have adopted the third model of power organization, known as the semi-presidential system. This challenge emerges from a justified apprehension regarding an overly strong executive branch and the attendant risks of systemic deformation into a personalized, unlimited, and arbitrary rule. The direct election of the president confers upon that office a legitimacy that is inherently stronger than that of the parliament, whose authority is essentially an aggregate of individually elected parliamentarians. In the national legal framework of the Republic of Serbia, the direct election of the president is a constitutional solution introduced with the advent of civic constitutionality and pluralism during the 1990s. Given the absence of a tradition involving a political system characterized by equitable rules between the government and the opposition, this modality led to a deformed constitutional democracy. Despite certain fluctuations during this period, there was a discernible tendency toward strengthening the role of the president and, at times, even achieving his absolute dominance over the executive branch as well as in relation to the legislative and the judicial branches. Since the election of the current president in 2017, this trend has evolved into a form of personal power that might be categorized as a “constitutional dictatorship.” The directly legitimized president, who concurrently serves as the leader of the most influential political party, has extended his authority over all three branches of government. Contrary to constitutional provisions, he has assumed the roles of both head of the executive and leader of the parliamentary majority, ultimately exerting influence over judicial bodies that are unable to operate independently because no branch of government is tasked with establishing the conditions necessary for an autonomous and impartial judiciary. The legal accountability of the president, as a fundamental republican principle, fails to yield the desired effect even in more developed constitutional democracies. The formal framework for holding the head of state accountable in Serbian national law suggests that the criminal accountability of the president for the gravest offense, namely “violation of the Constitution,” is too readily subsumed under political accountability, as it is determined by the parliamentary political majority. When one considers the underdeveloped structure of the Serbian parliament, characterized by a weakened and largely ineffectual opposition, as well as the absence of the requisite conditions for the operation of an independent judiciary, it becomes apparent that the procedure for removing the president of the Republic is entirely unfeasible.
Keywords: The separation of powers; The president of the Republic; The directly elected president; The criminal liability of president